A STUDY ON LISTENING PROBLEMS FACED BY STUDENTS OF HIGHER EDUCATION - Fergina Lengkoan; Fivy A. Andries; Devilito P. Tatipang (Universitas Muhammadiyah Tangerang, 2022)
The purpose of this study is to describe listening comprehension problems faced by students when taking the TOEFL-like test. This research is a descriptive research. This research is also categorized as a survey, the broad area of survey research encompasses any measurement procedures that involves asking questions of respondents. Furthermore, the researcher gave questions to the sample in form of questionnaire to get the data about listening problem faced by students taking TOEFL-like. In this research, the researcher used the questionnaire to collect the data. After discussion in the previous chapter, finally leads the researcher to make conclusion from what have been already discussed. The conclusion is among the twenty indicators, all the indicators came from various sides, such as: students' side, TOEFL organizer, material, listening equipment and another supported thing that related to the activity on TOEFL test especially listening skills.